Implementasi Ta'zir Edukatif dalam Meningkatkan Target Hafalan Al-Qur'an Santri Kelas 8 MTS di Pondok Pesantren Tahfidz Putra Roudhotul Qur'an Plandaan Jombang Tahun Ajaran 2023-2024 - Efendi, Soelton; Wafa, M. Aliyul; Nisa’, Khoirun (Lembaga Yasin AlSys, 2025)
Education in pesantren plays a crucial role in shaping the discipline and academic achievements of students, particularly in memorizing the Al-Qur’an. One of the methods applied is educational ta’zir, which refers to non-violent disciplinary measures aimed at education. The pesantren employs methods such as wahdah, takrir, and tasmi’, along with a quarantine system for students who face difficulties. This study aims to examine the implementation and effectiveness of educational ta’zir in improving the memorization of 8th-grade students at Pondok Pesantren Tahfidz Putra Roudhotul Qur’an Plandaan Jombang during the academic year 2023-2024. The research utilizes a qualitative descriptive method with techniques including observation, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the application of educational ta’zir significantly contributes to the enhancement of (1) motivation and enthusiasm, (2) discipline, (3) memorization speed, (4) memorization quality, and (5) the achievement of memorization targets among students. In conclusion, this research demonstrates that educational ta’zir is an effective method for improving student discipline and achieving Al-Qur’an memorization targets, while also fostering a more conducive learning environment in the pesantren. This study is expected to serve as a reference for other pesantren in implementing similar strategies to enhance the quality of education and Al-Qur’an memorization among student.